DECISION ON THE RATIONAL ALGORITHM IN TREATMENT OF KIDNEY CYSTS - A. V. Antonov; Ye. Yu. Ishutin; R. N. Guliev (Вестник хирургии имени И.И. Грекова)
The article presents an algorithm of diagnostics and treatment of renal cysts and other liquid neoplasms of the retroperitoneal space on an analysis of 270 case histories. The algorithm takes into account the achievements of modern medical technologies developed in the recent years. The application of the proposed algorithm must elevate efficiency of the diagnosis and quality of treatment of patients with renal cysts.